Effect of upper-airway stimulation for obstructive sleep apnoea on airway dimensions - Safiruddin, Faiza; Maurer, Joachim T. (The European respiratory journal, 2015)
Upper-airway stimulation (UAS) using a unilateral implantable neurostimulator for the hypoglossal nerve is an effective therapy for obstructive sleep apnoea patients with continuous positive airway pressure intolerance. This study evaluated stimulation effects on retropalatal and retrolingual dimensions during drug-induced sedation compared with wakefulness to assess mechanistic relationships in response to UAS. Patients with an implanted stimulator underwent nasal video endoscopy while awake and/or during drug-induced sedation in the supine position. The cross-sectional area, anterior-posterior and lateral dimensions of the retropalatal and retrolingual regions were measured during baseline and stimulation. 15 patients underwent endoscopy while awake and 12 underwent drug-induced sedation endoscopy. Increased levels of stimulation were associated with increased area of both the retropalatal and retrolingual regions. During wakefulness, a therapeutic level of stimulation increased the retropalatal area by 56.4% (p=0.002) and retrolingual area by 184.1% (p=0.006). During stimulation, the retropalatal area enlarged in the anterior-posterior dimension while retrolingual area enlarged in both anterior-posterior and lateral dimensions. During drug-induced sedation endoscopy, the same stimulation increased the retropalatal area by 180.0% (p=0.002) and retrolingual area by 130.1% (p=0.008). Therapy responders had larger retropalatal enlargement with stimulation than nonresponders. UAS increases both the retropalatal and retrolingual areas. This multilevel enlargement may explain reductions of the apnoea-hypopnoea index in selected patients receiving this therapy. Upper-airway stimulation for OSA increases airway dimensions at both the tongue base and the palate http://ow.ly/zZ4hk
Gesehen am: 14.08.2017